Penguatan Literasi Keagamaan Santri Dayah melalui Pelatihan Menulis Artikel Keislaman - Muhammad, Muhammad; Saputra, Dedi; Asman, Yunita; Ayunda, Desy Sary (Abdimas Indonesian Journal, 2025)
Islamic boarding schools (pesantren) play a crucial role in developing a knowledgeable and moral generation, yet religious literacy in many pesantren remains focused on the study of Islamic texts and has not been systematically directed toward writing skills. This community service program aims to strengthen the religious literacy of students through digital-based Islamic article writing training at Dayah Madinatuddiniyah Raudhatul Mubaarakah Al Munawwarah in Bireuen. The program was implemented from May to July 2025 and consisted of five main stages: outreach, training, technology implementation, evaluation, and program sustainability. The implementation results showed that students who were previously unfamiliar with formal writing were now able to produce more than five Islamic articles and religious opinions with improved writing structure. Furthermore, more than 30 pieces of visual content and articles were successfully published through the pesantren's blog and social media. The formation of a student writing community and the utilization of digital literacy spaces have strengthened the writing culture and opened up broader opportunities for digital da'wah. Thus, this activity demonstrates that students' writing skills can be significantly improved through structured training and the use of technology. This program strengthens the role of Islamic boarding schools as centers of Islamic education that are adaptive to digital developments while encouraging students to become producers of creative, moderate, and relevant Islamic content to the needs of society.